Hydrothermal Synthesis and Crystal Structure of A One-dimensional Zigzag Chain Based on 2,4’-Biphenyl-dicarboxylic Acid and 4,4’-Bipyridine - Wang, Aidong; Li, Wenbo; Guo, Feng; Zhang, Xiuling (Asian Journal of Chemistry, 2010)
Co-crystallization of 2,4'-biphenyl-dicarboxylic acid (2, 4'-dpa) and 4,4'-bipyridine (4,4'-bpy) was synthesized and characterized by X-ray diffraction at the orthorhombic, space group Pbca with a = 24.421(5), b = 9.055(10), c = 17.843(2) Å, Å3, Dc = 1.341 g/cm3 , F(000) = 1664 and Z = 8. There are one molecule of 2,4'- ziphenyldicarboxylic acid and 4,4'-bipyridine in the asymmetric unit. The dihedral angle between the pyridine ring planes is 2.40°. The intermolecular hydrogen bonds are observed in the compound.